2016
DOI: 10.1016/j.quascirev.2016.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical response of the mid-depth Northeast Atlantic Ocean to freshwater input during Heinrich events 1 to 4

Abstract: Introduction 3The climate of the last glacial period was punctuated by a number of pronounced events with near global impacts, known as Heinrich (or H-) events (e.g. Heinrich, 1988;Hemming, 2004). During these events, transient catastrophic collapses of the North American Laurentide Ice Sheet (LIS), centered over the Canadian Hudson Bay, produced armadas of icebergs that travelled through the Hudson Straight into the North AtlanticOcean, eventually depositing large volumes of ice-rafted debris (IRD), including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 184 publications
(231 reference statements)
2
9
0
Order By: Relevance
“…These sedimentological results agree with an active upper AMOC cell, although vertically contracted, persisting during the last glacial period as previously shown by various, independent geochemical proxies (i.e., benthic δ 13 C, ε Nd , Cd/Ca, 231 Pa/ 230 Th; Boyle & Keigwin, 1987; Curry & Oppo, 2005; Duplessy et al., 1988; Gherardi et al., 2009; Lippold et al., 2012; Marchitto & Broecker, 2006; Oppo & Lehman, 1993). This is also supported by our benthic δ 13 C data that show better ventilated waters during the glacial than the Holocene above ∼2,000 m whereas the opposite is observed below this depth (Figure ), in agreement with studies from both the European margin (Crocker et al., 2016; Peck et al., 2006; Willamowski & Zahn, 2000; Zahn et al., 1997) and the western North Atlantic (Curry & Oppo, 2005; Keigwin, 2004; Lynch‐Stieglitz et al., 2014; Zahn & Stüber, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These sedimentological results agree with an active upper AMOC cell, although vertically contracted, persisting during the last glacial period as previously shown by various, independent geochemical proxies (i.e., benthic δ 13 C, ε Nd , Cd/Ca, 231 Pa/ 230 Th; Boyle & Keigwin, 1987; Curry & Oppo, 2005; Duplessy et al., 1988; Gherardi et al., 2009; Lippold et al., 2012; Marchitto & Broecker, 2006; Oppo & Lehman, 1993). This is also supported by our benthic δ 13 C data that show better ventilated waters during the glacial than the Holocene above ∼2,000 m whereas the opposite is observed below this depth (Figure ), in agreement with studies from both the European margin (Crocker et al., 2016; Peck et al., 2006; Willamowski & Zahn, 2000; Zahn et al., 1997) and the western North Atlantic (Curry & Oppo, 2005; Keigwin, 2004; Lynch‐Stieglitz et al., 2014; Zahn & Stüber, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Our foraminiferal ε Nd records reveal core-top (i.e., upper Holocene) signatures of −10.6 ± 0.1 (n = 1) at ∼1,000 m and −11.3 ± 0.2 (n = 3) at 2,450 m (Figure 4d and Table S6). These ε Nd values are consistent with those of modern regional seawater and recent coral data from the French Atlantic margin (Copard et al, 2011;Dubois-Dauphin et al, 2017) as well as with foraminiferal data from the northern NE Atlantic (Crocker et al, 2016;Roberts & Piotrowski, 2015). Our results thus capture the modern regional water mass structure of the NE Atlantic with MOW overlying well-mixed NADW ( Figure S9).…”
Section: Bottom-water Chemistrysupporting
confidence: 89%
See 1 more Smart Citation
“…Taking into account the southward shifted and reduced deep water formation in the Greenland Sea during the LGM, Iceland Scotland Overflow Water (ISOW), and Denmark Strait Overflow Water may have been weakened and shoaled (Fagel et al, ; Millo et al, ). Two studies suggested persistent overflow from the GIN Seas during the LGM reporting water with relatively high εNd passing the Wyville‐Thomson Ridge (Crocker et al, ; Crocket et al, ). However, if this water mass indeed descended deep enough in the subpolar North Atlantic moving as a deep boundary current analogous to today, it would first have passed through the Labrador Sea where it would have been admixed into less radiogenic deep waters.…”
Section: Resultsmentioning
confidence: 99%
“…This suggestion invokes a deep Eastern Atlantic route for this water-20 mass to the Angola Basin. This possibility cannot be ruled out for our study intervals based on our Nd data alone because today both Nordic Sea overflows and AABW share a radiogenic Nd signature (of ~ -7 to -9; Crocker et al, 2016). Yet [CO3 2-] is markedly higher for modern NGS overflow water (>115 µmol kg -1 ) than for SCW (~85 µmol kg -1 ) and this contrast would have been greater during the Last Glacial Maximum than today (Yu et al, 2008;Crocker et al, 2016).…”
Section: Deep Atlantic Ocean Structure During the Last Glacial-holocenementioning
confidence: 94%